The association between dietary total antioxidant capacity and hearing loss: results from the Tehran employees Cohort Study - Batoul Ghosn; Leila Azadbakht; Mohammad Reza Monazzam Esmaeilpour; Ahmad Esmaillzadeh (BMC, 2024)
Abstract Background Despite numerous studies that have explored the association between individual antioxidants or specific combinations and the risk of hearing loss, there is lack of information regarding the relationship between dietary total antioxidant capacity (dTAC) and hearing loss. The conflicting results on this association further highlight the need for more research in this area. This study aims to investigate the association between overall dietary antioxidant intake and the risk of hearing loss among Iranian adults. Methods This cross-sectional study recruited 3443 adult participants aged between 19 and 67 years (with an average age of 41.4 years ± 8.8) who were employed at Tehran University of Medical Sciences in Iran. Participants underwent dietary assessment using a validated Food Frequency Questionnaire (FFQ). The hearing status of each participant was evaluated by a licensed audiologist in a soundproof room, using diagnostic audiometry that adhered to American National Standards specifications and followed standard audiometric clinical procedures. The dietary total antioxidant capacity (dTAC) was calculated using the Ferric Reducing-Antioxidant Power (FRAP) values. Results 43.6% of male participants had hearing loss, while 26.8% among female participants. After accounting for various confounding factors, no significant association was observed between higher levels of dTAC and reduced odds of hearing loss in the overall population. However, among men under the age of 40, higher levels of dTAC were associated with decreased odds of hearing loss, even after adjusting for several covariates (OR: 0.56, 95% CI: 0.31-1.02, Ptrend = 0.02). This relationship was not evident in men over 40 years of age or among women. Conclusion The study found an inverse relationship between higher antioxidant intake in the diet and lower odds of hearing loss, specifically among men who were 40 years old or younger. However, this relationship was not observed in the overall population or among women. Additional prospective studies are necessary to validate these results.